Knowledge and Perception of Marital Rape in Pakistan - Huzaifa Sarfraz; Munazza Madani; Riaz Ahmed Shaikh (International Journal on Women Empowerment, 2020)
Background: In Pakistan, marital rape is not an immediate concern because domestic violence like battering one's wife is considered a private matter. In Pakistan, marital rape is a concept of which the majority are not even aware. Being a society where violence against women is widespread, it is imperative to study the perception and awareness level of marital rape in Pakistan. This study was designed to understand the perception of marital rape among women living in Karachi. Methodology: The present study is exploratory; based on saturation, the researcher conducted in-depth interviews with eleven participants. The researcher has analyzed the qualitative data by following Creswell Model (2014). Results: Findings of the study revealed that marital rape is rarely known among women living in Karachi, and the institution of the family plays a very weak role in providing sex education to their girls. Conclusion: This study has concluded that there are no sources in Pakistan that can provide awareness regarding women's sexual rights except family.